A study on the content of integrity policies and research integrity management in Chinese universities - Cao, Yuan; Jiang, Yuwei; Zhao, Yong (Frontiers in Research Metrics and Analytics, 2023)
This study outlines a comprehensive analysis of the primary characteristics of managing research integrity (RI) in domestic colleges and universities in China. RI education consists primarily of soft advocacy, with no hard requirements or continuous and systematic support. Colleges and universities are the vital actors that establish and administer RI regulation. However, the literature on the regulation of RI policies in China’s universities is very limited. For this reason, we investigate this topic by choosing the top 50 universities in the 2021 Best Chinese Universities Rankin. By integrating the use of scientometrics analysis, policy analysis, policy measurement, and inductive analysis, we examine whether and how these schools respond to national policies in a timely manner, especially in terms of their frequency of updates, topic clustering analysis, terms clustering analysis, content aggregation, and composition of RI management committees. RI management in China’s universities has established management policies and working mechanisms, reached a consensus on research misconduct, and clarified its main challenges. Yet, there is still a need to further define research misconduct, improve RI policies, and optimize RI management.